Analysis of investment attractiveness of land plots on the territory of Cherkasy region - Riabova, Y. (Land Management, Cadastre and Land Monitoring, 2024)
Studying the issue of investment attractiveness of land plots is quite relevant, since land resources are an important asset for investors and regional development. Due to the constant growth of interest in investment in land plots, the analysis of their attractiveness is becoming a key task for regional development and economic growth.The article presents the results of a study of the investment attractiveness of land plots in the Cherkasy region, which involved an analysis of a wide range of factors influencing investors' decisions to invest in the land resources of the selected region.The economic, social and infrastructural aspects of land use in Cherkasy region were analyzed in order to determine the overall investment attractiveness. Particular attention is paid to the analysis of potential opportunities for the development of sustainable land use and balanced use of land resources in the region.The dynamics of land relations in the region is revealed, taking into account their retrospective and current trends. The legal environment for regulating land relations and its impact on investment activity in the region is analyzed, which made it possible to more broadly assess the attractiveness of Cherkasy region for investment in land plots.The results of the study can be used as a basis for investors' investment strategies, as well as serve as a basis for justifying decisions regarding investments in land assets in Cherkasy region.Keywords: investment, investment potential, sustainable land use, balanced use of land resources, efficiency of land use, economic development, real estate market, legislation, investment opportunities.
Keywords: Investment; investment potential; sustainable land use; balanced use of land resources; efficiency of land use; economic development; real estate market; legislation; investment opportunities